Impact Evaluation of the National Crime Victim Law Institute's Victims' Rights Clinics, 2009-2010 (United States) - Davis, Robert C. ([Verlag nicht ermittelbar], 2016)
These data are part of NACJD's Fast Track Release and are distributed as they were received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except for the removal of direct identifiers. Users should refer to the accompanying readme file for a brief description of the files available with this collection and consult the investigator(s) if further information is needed.The purpose of the impact evaluation was to gauge the success of the victim's rights clinics in attaining each of the following goals Aid in enforcing rights for individual victims and getting them help for crime-related needs, thereby increasing satisfaction of victims with the justice process; Change attitudes of criminal justice officials towards victims' rights and increase their knowledge about rights; Change the legal landscape: establish victim standing and develop positive case law; Increase compliance of criminal justice officials with victims' rights; and Sustain the clinic through developing alternative sources of funding Researchers conducted surveys with prosecutors, judges, victim advocates, and defense attorneys to determine whether they had changed their attitudes toward victims' rights since the local clinic opened its doors. Surveys were fielded in South Carolina, Maryland, and Utah (Criminal Justice Official data, n=552) where clinic evaluations were conducted. An additional survey was fielded in Colorado (Colorado data, n=583) where the victim rights clinic had not yet started to accept cases. To determine the effect that clinics had on observance of victims' rights, researchers collected three samples of cases from prosecutors (NCVLI Case File Data, n=757) in the jurisdiction or jurisdictions in which each local clinic had done the most work: (a) all clinic cases closed since the start of each local clinic; (b) cases closed during the most recent 12-month period which did not involve representation by a clinic attorney; and (c) cases closed in the year prior to the start of each local clinic. Finally, to assess the impact of the clinics on victims' satisfaction with the criminal justice process and its compliance with their rights, researchers conducted telephone interviews (Victim Survey Data, n=125) with two samples of victims in each evaluation site, one drawn from the sample of cases at prosecutor offices and one drawn from the crime victim legal clinics.